Wide QRS complex tachycardia and alternating bundle branch block aberration: What is the mechanism?. Issue 3 (31st March 2022) - Iwakawa, Hidehiro; Terata, Ken; Tashiro, Haruwo; Abe, Yoshihisa; Watanabe, Hiroyuki
Abstract : A 70‐year‐old man was referred for evaluation and treatment of wide QRS complex tachycardia with left bundle branch block morphology. Electrocardiography showed atrial bigeminy with an alternating bundle branch block (ABBB) aberration. Atrial burst stimulation reproducibly demonstrated ABBB. What is the mechanism?